Glucose variability in 6–12-month-old healthy infants - Hauschild, Michael; Monnard, Cathriona; Eldridge, Alison L.; Antoniou, Maria Christina; Bouthors, Thérèse; Hansen, Erik; Dwyer, Andrew A.; Rytz, Andreas; Darimont, Christian (Frontiers in Nutrition, 2023)
Background: Metabolic programming of glucose homeostasis in the first 1,000 days of life may impact lifelong metabolic and cardiovascular health. Continuous glucose monitoring (CGM) devices may help measure the impact of dietary intake on glucose rhythms and metabolism in infants during the complementary feeding period. Objectives: Demonstrate the feasibility of CGM to measure and quantify glucose variability in response to infant feeding and to evaluate associations between macronutrient meal composition and glucose variability. Methods: The “FreeStyle Libre Pro®” device interstitial glucose meter was applied to the anterior thigh of 10 healthy 6–12-month-old infants. Parents recorded food intake, time of feeding, and used daily dairies to record sleep time and duration. Descriptive statistics were employed for food intake, sleep and key glycemic parameters over three full days. Mixed linear models were used to assess glycemic changes. Results: Mid-day, afternoon, and evening feeds contained >30g carbohydrate and induced higher 2-hour iAUC (3.42, 3.41 and 3.50 mmol/L*h respectively) compared to early and mid-morning feedings with ≤ 25g carbohydrates (iAUC 2.72 and 2.81 mmol/L*h, p<0.05). Early morning and evening milk feedings contained approximately 9g of fat and induced a longer time to reach maximal glucose value (Tmax; 75 and 68 minutes, respectively) compared to lower fat feedings (2.9–5.9g; Tmax range: 34–60 minutes; p<0.05). Incremental glucose value at time of food intake (C0) increased significantly from 0.24±0.39 mM in early morning to 1.07±0.57 mM in the evening (p<0.05). Over the day, 70% of glucose values remained within the normal range (3.5–5.5 mmol/L), 10% were between 5.5–10 mmol/L, and 20% were <3.5 mmol/L. Conclusions: Our data support the feasibility of using CGM to measure glucose in 6–12-month-old infants. The observation of possible diurnal glucose variability and typical glucose values may have implications for future studies investigating metabolic adaptation to nutritional intake in early life.